A glimpse beneath Antarctic sea ice: Platelet layer volume from multifrequency electromagnetic induction sounding. Issue 1 (9th January 2016) - Hunkeler, P. A.; Hoppmann, M.; Hendricks, S.; Kalscheuer, T.; Gerdes, R.
Abstract: In Antarctica, ice crystals emerge from ice shelf cavities and accumulate in unconsolidated layers beneath nearby sea ice. Such sub‐ice platelet layers form a unique habitat and serve as an indicator for the state of an ice shelf. However, the lack of a suitable methodology impedes an efficient quantification of this phenomenon on scales beyond point measurements. In this study, we inverted multifrequency electromagnetic (EM) induction soundings, obtained on fast ice with an underlying platelet layer along profiles of 100 km length in the eastern Weddell Sea. EM‐derived platelet layer thickness and conductivity are consistent with other field observations. Our results suggest that platelet layer volume is higher than previously thought in this region and that platelet layer ice volume fraction is proportional to its thickness. We conclude that multifrequency EM is a suitable tool to determine platelet layer volume, with the potential to obtain crucial knowledge of associated processes in otherwise inaccessible ice shelf cavities. Key Points: We present the first EM‐based platelet layer thickness and conductivity data set Multifrequency EM data inversion enables platelet layer volume estimates A thicker platelet layer has a higher ice volume fraction